Gestión del cambio organizacional - Duarte Hablutzel, Milenka (2020)
Currently, organizations are under pressure to create changes in their objectives, structures and processes in order to align with the demands of the global market. The only way to survive these demands is to implement effective change management. Because of the importance of change management, different theoretical models have emerged, which help determine how to implement change management in the best possible way in order to guarantee organizational success. However, change management in the public sector faces great difficulties, as these entities have more obstacles in relation to accomplishing their goals. Because of this, the current state of the art aims to present the latest research regarding change management in the public sector, and specifically variables that lead to its effectiveness. This state of the art considers a series of models from various theoretical and psychological perspectives, as well as recent information from international and national research carried out in the last five years. Additionally, different variables that affect change management have been identified, which can have a positive or negative effect in this process. These include organizational (climate, quality of life, strategic planning, organizational hierarchy), individual (compromise, resistance, participation, attitude, perception), and training-related (leadership, communication, training, teamwork) factors. In light of these findings, it is vital that future research focuses on the growing role of psychologists as facilitators of organizational change, and on new tendencies such as inverse change theory and the organizational constellations technique.